2021
DOI: 10.1002/pros.24108
|View full text |Cite
|
Sign up to set email alerts
|

Transcript analysis of commercial prostate cancer risk stratification panels in hard‐to‐predict grade group 2–4 prostate cancers

Abstract: Background Improved prognostication is needed to minimize overtreatment in grade group (GG) 2–4 prostate cancer. Our aim was to determine, at messenger RNA (mRNA) level, the performance of the genes in the commercial panels Decipher, Oncotype DX, Prolaris, and mutational panel MSK‐IMPACT to predict metastasis‐free and prostate cancer‐specific death (PCSD) in patients with GG 2–4 prostate cancer at radical prostatectomy. Methods The retrospective cohort consisted of GG 2–4 patients treated with radical prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…When KLKs and PARs were used as a panel with or without clinical parameters (GG, pathological stage and PSA), they improved classification of metastatic PCa and lethal disease. The demonstrated classification performance was similar to that of publicly available genes included in commercially available PCa risk stratification panels in our previous study 34 …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…When KLKs and PARs were used as a panel with or without clinical parameters (GG, pathological stage and PSA), they improved classification of metastatic PCa and lethal disease. The demonstrated classification performance was similar to that of publicly available genes included in commercially available PCa risk stratification panels in our previous study 34 …”
Section: Discussionsupporting
confidence: 79%
“…The primary case‐control study for mRNA analyses consisted of 165 GG2‐4 patients treated by radical prostatectomy in Helsinki University Hospital in 1992‐2015. The selection process of patients has been previously described 34 . Seventy‐nine patients with metastatic progression or PCa‐specific death, during the median follow‐up of 11 years, were selected to present cases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the tissue-based biomarker tests discussed, Oncotype DX Prostate, ProMark, Decipher and Prolaris are the best validated thus far. While these tissue-based biomarker assays have the potential to influence the management of PC patients, there are a number of issues that are currently restricting their use: (i) Direct comparison of Oncotype DX, Prolaris and Decipher to one another has shown that prognostic outcomes can differ depending on the test used [ 353 , 354 ]. (ii) Many of these assays were developed and initially validated in cohorts of patients who were mostly white European or white American men, with limited initial research performed into the value of these tests in African American men, who are recognised as having poorer outcomes.…”
Section: Limitations and Future Perspectives Of Pc Biomarker Assaysmentioning
confidence: 99%